Crosslinking of polyolefin foam. III. Increasing low density polyethylene foam production efficiency by incorporation of polyfunctional monomers - Coswald Stephen Sipaut @ Mohd Nasri; G. L. A. Sims; M. N. Mohamad Ibrahim (RAPRA Technology Ltd., 2007)
The effect of introducing polyfunctional monomers into dicumyl peroxide (DCP) crosslinking systems for low-density polyethylene (LDPE) is considered. Effects are characterised as a function of relative concentrations in solid, melt and foamed states. The monomers selected were diallyl phthalate (DALP), trimethylolpropane trimethacrylate (TMPTMA) and triallyl cyanurate (TAC). It is shown that TAC promotes network formation more efficiently than TMPTMA and DALP allowing a considerable reduction in DCP concentration to attain a specific gel content. A TAC concentration of approximately 0.5% was most cost-effective. Crosslinking promotion efficiency was shown to be in the order TAC > DALP > TMPTMA. Polyfunctional monomers containing allyl groups appeared to be significantly more effective than methacrylates and the efficiency improved with increasing functionality. Compression moulding of LDPE foams of similar density showed that the cycle time could be reduced using a DCP/TAC system compared with DCP alone.